Towards a biomarker model for cognitive improvement: No change in memory-related prefrontal engagement following a negative cognitive remediation trial in bipolar disorder. (October 2018) - Macoveanu, Julian; Demant, Kirsa M; Vinberg, Maj; Siebner, Hartwig R; Kessing, Lars V; Miskowiak, Kamilla W
Background: Cognitive deficits are prevalent in bipolar disorder during remission but effective cognition treatments are lacking due to insufficient insight into the neurobiological targets of cognitive improvement. Emerging data suggest that dorsal prefrontal cortex target engagement is a key neurocircuitry biomarker of pro-cognitive treatment effects. Aims: In this randomized controlled functional magnetic resonance imaging study, we test this hypothesis by investigating the effects of an ineffective cognitive remediation intervention on dorsal prefrontal response during strategic memory encoding and working memory engagement. Methods: Bipolar disorder patients in partial remission with subjective cognitive difficulties were randomized to receive 12-week group-based cognitive remediation ( n = 13) or to continue their standard treatment ( n = 14). The patients performed a strategic episodic picture encoding task and a spatial n-back working memory task under functional magnetic resonance imaging at baseline and following cognitive remediation or standard treatment. Results: The right dorsolateral prefrontal cortex was commonly activated by both strategic memory tasks across all patients. The task-related prefrontal engagement was not altered by cognitive remediation relative to standard treatment. The dorsolateral prefrontal cortex response was not significantly associated with recall accuracy or working memory performance. Conclusions: As hypothesized, no task-related change in prefrontal activity was observed in a negative cognitive remediation trial in remitted bipolar disorder patients. By complementing previous findings linking cognitive improvement with increased dorsolateral prefrontal cortex engagement, our negative findings provide additional validity evidence to the dorsal prefrontal target engagement biomarker model of cognitive improvement by strengthening the proposed causality between modulation of dorsolateral prefrontal cortex engagement and pro-cognitive effects.